PRAKTOGNOSIA: ECOSOPHICAL REMARKS ON HAVING A BODY - De Fazio, Gianluca; Lévano, Paulo (Revista Tempos e Espaços em Educação, 2019)
The authors trace the question “what can a body do?” back to one of the main conceptual lines of discussion featured in the history of modern thought, namely, the nature/culture distinction, closely linked to the object/subject and natural/artificial distinctions. These distinctions being the core of important developments in 20th-century French philosophical thought, a specific reference will be carried out to the works of philosophers Maurice Merleau-Ponty and Georges Canguilhem, dealing respectively with praktognosia and biological normativity. Having them in mind, the authors aim at relieving the body from the conceptual imagery provoked by yet another product of the nature/culture distinction: the mind/body dualism, which very often has submitted the latter to the former. Departing from the description of the ecosophical context assigned to the content of this article, the conclusive remarks hope for an ecologically renewed conceptualization of the body and its range of action.